2018
DOI: 10.3892/br.2018.1058
|View full text |Cite
|
Sign up to set email alerts
|

Ristocetin induces phosphorylated‑HSP27 (HSPB1) release from the platelets of type 2 DM patients: Anti‑platelet agent‑effect on the release

Abstract: Abstract. It has been previously reported that HSP27 is released from platelets in type 2 diabetes mellitus (DM) patients according to phosphorylation. In the present study, we investigated the effect of ristocetin, a glycoprotein (GP) Ib/IX/V activator, on the release of HSP27 and the effect of anti-platelet agents, such as acetylsalicylic acid (ASA), on this release. Forty-six patients with type 2 DM were recruited, and classified into two groups depending on administration of anti-platelet agents, resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Thermal stress has been demonstrated to increase the amount of secreted HSPA1 from astrocytes (Taylor et al, 2007) and HEPG2 cells (Vega et al, 2008). Moreover, a recent study showed the release of phosphorylated HSPB1 from aggregating human platelets (Tokuda et al, 2018). Therefore, we can suppose that stress protein release may have important regulatory roles under physiological and pathological conditions (Calderwood et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal stress has been demonstrated to increase the amount of secreted HSPA1 from astrocytes (Taylor et al, 2007) and HEPG2 cells (Vega et al, 2008). Moreover, a recent study showed the release of phosphorylated HSPB1 from aggregating human platelets (Tokuda et al, 2018). Therefore, we can suppose that stress protein release may have important regulatory roles under physiological and pathological conditions (Calderwood et al, 2007).…”
Section: Introductionmentioning
confidence: 99%